Uses of chitosan-based hydrogels in dentistry : a systematic review = Usos de hidrogeles a base de quitosano en odontología : una revisión sistemática - Valenciana Solís, Jesús Antonio
The objective of this article was to carry out a systematic review of the literature to determine the different therapeutic uses of chitosan-based hydrogels and their uses in dental therapy, as well as the modification and improvement of dental materials to promote research related to chitosan and its incorporation into dentistry as an adjunct or replacement in some dental treatments. Chitosan is a natural polymer obtained from the deacetylation of chitin, a polysaccharide abundant in nature, which, due to its biocompatibility, high biodegradability, non-antigenicity, and its ease of acquisition, has attracted biomedical interest, including in dentistry. Recent studies have shown that chitosan can be integrated into dental materials to obtain remineralizing effects, such as for antimicrobial agents, osteogenic agents, and pulp regeneration treatment. A bibliographic search was carried out in PubMed from 2018 to 2023. The results showed a wide range of uses for chitosan in the dental field, particularly its use as a remineralizing agent for tooth enamel; It has also been used in tissue regeneration mainly because of its osteogenic activity, as an antimicrobial agent, and as a vehicle for the application of medications. The use of chitosan as a nanobiomaterial is an interesting topic, since chitosan shows potential for new dental materials, either as an active ingredient or as an adjuvant vehicle for other materials.